Association between coffee and tea consumption and the risk of macrovascular complications in type 2 diabetes: a UK Biobank cohort study - Ting Ma; Lingling Yang; Miaomiao Wu; Bo Wang; Jiangping Li; Jiafei Yang; Xian Sun (Diabetology & Metabolic Syndrome)
Abstract Background Many studies have shown that coffee and tea consumption is associated with diabetes. However, limited research exists on their effects on the risk of macrovascular complications in diabetic patients. Therefore, the purpose of this study was to examine the relationship between the intake of coffee and tea and macrovascular complications in patients with type 2 diabetes mellitus (T2DM). Methods We used the Cox proportional hazards regression model to estimate the hazard ratio (HR) and 95% confidence interval (CI), which determined the relationship between coffee and tea consumption and the risk of macrovascular complications among 14,277 UK Biobank participants. Results Compared with non-coffee or tea drinkers, those who consumed 0.5–1 cup of coffee (HR 0.67,95% CI 0.518 to 0.856) or 2–4 cups of tea (HR 0.66,95% CI 0.524 to 0.839) per day had the lowest risk of stroke; daily intake of 2–4 cups of coffee associated with reduced risk of angina pectoris (AP) (HR 0.82,95% CI 0.726 to 0.916); those who consumed 0.5–1 cup of tea per day had the lowest risk of the heart failure (HF) (HR 0.73,95% CI 0.602 to 0.879); furthermore, those who consumed 2–4 cups of coffee and 0.5–1 cup of tea per day (HR 0.55, 95% CI 0.379–0.790) demonstrated the lowest risk of HF onset compared with those who did not consume coffee and tea at all. Conclusions This study found that in a T2DM population, moderate coffee consumption significantly lowered the risk of stroke and AP, while moderate tea intake reduced the risk of stroke and HF. Combined moderate consumption of both beverages provided optimal protection against HF.